Sonochemical action and reaction of edible insect protein: Influence on enzymolysis reaction‐kinetics, free‐Gibbs, structure, and antioxidant capacity - Mintah, B.K.; He, R.; Dabbour, M.; Agyekum, A.A.; Xing, Z.; Golly, M.K.; Ma, H. (journal of Food Biochemistry, 2019)
We investigated the impact of sonochemical action and the reaction of Hermetia illucens larvae meal protein (HILMP) as regards enzymolysis under varied enzyme concentration and temperature to explain the mechanism and effect of sonication on molecular conformation, limits of kinetics, free‐Gibbs energy, and antioxidative capacity. Control treatment was used for comparison. The results showed sonochemical treatment enhanced HILMP‐enzymolysis efficiency at various enzyme volume, and temperature. Enzymolysis‐kinetics revealed sonochemical treatment increased the rate constant (p < .05) by 17.21%, 25.06%, 26.91%, and 41.38% at 323, 313, 303, and 293 K, respectively. On free‐Gibbs, sonochemical treatment reduced the reactantsreactivity energy, enthalpy, and entropy by 30.53%, 35.05%, and 10.71%, respectively (p < .05). Changes in spectra of UV and fluorescence, and micrographic imaging indicated alterations of HILMP by sonochemical treatment. Antioxidative activity of sonochemically‐treated HILMP increased, compared to control. Thus, sonochemical treatment may be beneficial in the production of edible insect proteins with smaller molecular weights for different food and/or pharmaceutical applications.
Research Article
Keywords: Antioxidant activity; Edible insect protein; Enzymolysis reactivity energy; Molecular Conformation; Sonochemical treatment